Quantitative determination of carbasalate calcium derived metabolites, acetylsalicylic acid and salicylic acid, in six animal foods using liquid-liquid extraction method coupled with liquid chromatography-tandem mass spectrometry. (25th April 2019) - Zheng, Weijia; Yoo, Kyung-Hee; Abd El-Aty, A.M.; Park, Da-Hee; Choi, Jeong-Min; Kim, Seong-Kwan; Kang, Young-Sun; Zhang, Hongxia; Hacımüftüoğlu, Ahmet; Bekhit, Alaa El-Din; Wang, Jing; Shim, Jae-Han; et al.
Graphical abstract: Highlights: An analytical method was developed for detecting acetylsalicylic acid and salicylic acid. The target analytes were extracted from six animal foods, including porcine muscle, milk, egg, shrimp, eel, and flatfish. Acetonitrile acidified with formic acid and trifluoroacetic acid was used as the extraction solvent. The method performance was satisfactory for both tested analytes in various matrices. The obtained results could assist the regulatory authority in drafting the MRL for the tested analytes. Abstract: This work describes a simple screening protocol for quantification of carbasalate calcium derived metabolites, acetylsalicylic acid (ASA) and salicylic acid (SA), in animal and aquatic food matrices using liquid chromatography-tandem mass spectrometry (LC-MS/MS). The analytes were extracted from porcine muscle, milk, egg, shrimp, eel, and flatfish using acetonitrile, with the addition of formic acid as well as trifluoroacetic acid, followed by liquid-liquid purification with saturated n -hexane. A reverse-phase analytical column was employed with a mobile phase comprising (A) 1 mM ammonium acetate in distilled water and (B) methanol to achieve the best chromatographic separation. Matrix-matched calibration curves ( R 2  ≥ 0.9817) were constructed using six concentrations of 5, 10, 20, 30, 40, and 50 µg/kg in porcine muscle, milk, egg, shrimp, eel, and flatfish matrices. The calculated limits of quantification (LOQ) were 10 and 7 µg/kg, for ASA and SA, respectively. Recoveries of 67 to 102% with relative standard deviations (RSDs) of ≤9.0% (intra-day and inter-day) were obtained for all matrices at four spiking concentrations (5, 10, 20, and 50 µg/kg). The method was feasibly applied for monitoring market samples. In conclusion, the developed method is versatile, accurate, and precise for detecting and quantifying acetylsalicylic acid and salicylic acid residues in animal-derived foods meant for human consumption.